Hydroxamate Recognition During Iron Transport from Hydroxamate-Iron Chelates - Haydon, A. H. (1973)
Kinetics of radioactive iron transport from three structurally different secondary hydroxamate-iron chelates (schizokinen-iron, produced by Bacillus megaterium ATCC 19213; Desferal-iron, produced by an actinomycete; and aerobactin-iron, produced by Aerobacter aerogenes 62-1) revealed that B. megaterium SK11 (a mutant which cannot synthesize schizokinen) has a specific transport system for utilization of ferric hydroxamates with a recognition capacity based on the chemical structure of the hydroxamate. Both Desferal and schizokinen enhanced iron uptake in this organism; however, Desferal-iron delivered only one-sixth the level of iron incorporated from the schizokinen-iron chelate. Desferal-iron did not generate the rapid rates of iron transport noted with schizokinen-iron at elevated iron concentrations. Assays containing large excesses of either iron-free Desferal or iron-free schizokinen suggested that the iron-free hydroxamate may compete with the ferric hydroxamate for acceptance by the transport system although the system has greater affinity for the iron chelate. Aerobactin-iron did not stimulate iron uptake in B. megaterium SK11 and aerobactin inhibited growth of this organism, indicating that B. megaterium SK11 cannot efficiently process the aerobactin-iron chelate.